ARRANGEMENT OF PERFORMANCE MEASUREMENT TOOLSWITH HUMAN SCORECARD METHOD IN XYZ GENERAL HOSPITAL - Rambu Kanyaku, Yuricka Priskilia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
XYZ Hospital in effort to improve its human resources quality only conduct competency assessment only. The hospitals so far have not focused on measuring the human resources performance comprehensively or thoroughly so it is not known what factors have not been achieved to form good employee performance quality in addition to employee competence. For that, it needs study to analyze employee performance measurement through approach of correlation between company strategy and human resource strategy in achieving company performance. The Human Resource Scorecard contains key performance indicators that can present the performance of human resources to reach corporate objectives. This study will be limited to the arrangement of organizational performance indicators with the HR scorecard model. This research was conducted in the personnel department of XYZ General Hospital. Identification of measurement aspects was based on the companyvision, mission, and strategic direction. Keywords: Performance assessment, Balance Scorecard (BSC), Key Performance Indicator (KPI)